The Bhutan Electric Vehicle Initiative : Scenarios, Implications, and Economic Impact - Zhu, Da; Patella, Dominic Pasquale; Steinmetz, Roland; Peamsilpakulchorn, Pajnapa (Washington, DC: World Bank, 2016)
This report aims to help Bhutan think through various technical and policy issues of introducing electric vehicles in its own context. It analyses a variety of factors that will impact adoption of electric vehicles from technical, market and financial feasibility to consumer awareness and stakeholders’ capacity. It also addresses several policy questions which are at the heart of public debate such as affordability of the government to undertake the program, economic costs and benefits, distributional impact, fiscal, and macroeconomic implications.